Hsa_circ_0005915 promotes N, N-dimethylformamide-induced oxidative stress in HL-7702 cells through NRF2/ARE axis. (30th June 2021) - Liu, Ziqi; He, Qianmei; Liu, Ye; Zhang, Yangchun; Cui, Mengxing; Peng, Honghao; Wang, Yuqing; Chen, Shen; Li, Daochuan; Chen, Liping; Xiao, Yongmei; Chen, Wen; et al.
Graphical abstract: hsa_circ_0005915 was significantly up-regulated, which inducing degradation of NRF2 protein. Consequently, NRF2-downstream anti-oxidative gene (HO1 and NQO1) expression was inhibited, which inducing oxidative stress in hepatocytes. Graph was drawn using Adobe Illustrator software (Adobe Systems Incorporated, CA, USA). Abstract: N, N -dimethylformamide (DMF) is an organic compound widely used in industrial production processes as a solvent with a low evaporation rate. Excessive exposure to DMF may lead to liver damage. Oxidative stress has been reported as one of the main causes of DMF-induced hepatotoxicity. Several doses of DMF (0, 1, 5, and 10 mM) were used to treat HL-7702 cells for a relatively long period to simulate the actual exposure pattern in occupational settings, and oxidative stress was induced. Previous studies illustrated that circular RNA (circRNA) plays a vital role in sustaining hepatocyte physiological function. To explore whether aberrant circRNA expression is involved in DMF-induced excessive ROS generation and hepatotoxicity, high-throughput transcriptional sequencing was performed to identify the altered circRNA expression profiles in HL-7702 liver cells after treatment with 0, 75, or 150 mM DMF for 48 h. We found that levels of induced oxidative stress were similar to those in the long-term exposure model. Among the altered circRNAs, one circRNA (hsa_circ_0005915) was significantly upregulated after DMF exposure, and it affected DMF-mediated oxidative stress in HL-7702 cells. Further experiments revealed that hsa_circ_0005915 downregulated the expression of nuclear factor erythoid-2-related factor 2 (NRF2) at the post-transcriptional level via promoting the ubiquitination and degradation of NRF2, which led to the increase of ROS accumulation. Further investigation demonstrated that the expression levels of NRF2-regulated antioxidative genes—heme oxygenase 1 (HO1) and NAD(P)H quinone dehydrogenase 1 (NQO1)—indeed declined after the overexpression of hsa_circ_0005915. In vivo study also indicated that DMF exposure can upregulate the expression of mmu_circ_0007941 (homologous circRNA of hsa_circ_0005915) and downregulated Nrf2 and Ho1 proteins. In summary, our results revealed that hsa_circ_0005915 plays an important role in promoting DMF-induced oxidative stress by inhibiting the transcriptional activity of the NRF2/ARE axis, which provides a potential molecular mechanism of DMF-mediated hepatotoxicity.